LEXICAL ATTRIBUTES OF SLANG (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This scholarly investigation delves into the lexical properties inherent in slang, an omnipresent linguistic phenomenon distinguished by its informal and nontraditional lexicon usage. By scrutinizing diverse linguistic elements, this research endeavors to elucidate the distinctive lexical traits of slang and their ramifications on language dynamics and socio-cultural environments.